4z+3=6+2z solve and check
Answers
Answered by
219
Hello friend
Good morning
⭐⭐⭐⭐⭐⭐⭐⭐⭐⭐⭐⭐⭐⭐
Ques. 4z + 3 = 6 + 2 z
Solution:
➡️=> 4z + 3 = 6 + 2z
➡️=> 4z - 2z = 6 - 3
➡️=> 2z = 3
➡️=> z = 3 / 2
Verification
➡️Z = 3 / 2 given
➡️=> 4 × 3/ 2 + 3 = 6 + 2 × 3 / 2
➡️=> 2 ×3 + 3 = 6 + 3
➡️=> 9 = 9 verified
⭐⭐⭐⭐⭐⭐⭐⭐⭐⭐⭐⭐⭐
I hope it will help you a lot
Thanks
@drsm
Good morning
⭐⭐⭐⭐⭐⭐⭐⭐⭐⭐⭐⭐⭐⭐
Ques. 4z + 3 = 6 + 2 z
Solution:
➡️=> 4z + 3 = 6 + 2z
➡️=> 4z - 2z = 6 - 3
➡️=> 2z = 3
➡️=> z = 3 / 2
Verification
➡️Z = 3 / 2 given
➡️=> 4 × 3/ 2 + 3 = 6 + 2 × 3 / 2
➡️=> 2 ×3 + 3 = 6 + 3
➡️=> 9 = 9 verified
⭐⭐⭐⭐⭐⭐⭐⭐⭐⭐⭐⭐⭐
I hope it will help you a lot
Thanks
@drsm
abhil:
Thank you friend
Answered by
5
Answer:
=>
Step-by-step explanation:
Given that:-
To find:- The value of the expression:
Here we will use the transposition method.
First of all, we have to identify the variables and the constants.
Then solve the expression of both sides by using various mathematical operations.
As we have,
=>
Rearrange the terms,
=>
Subtract both sides by :
=>
=>
Now, subtract both sides by :
=>
=>
Divide both sides by :
=>
Hence, the required solution is .
Similar questions
Science,
1 year ago